The clinicopathological profile of Renal cell carcinoma at BP Koirala Memorial Cancer Hospital - Pokhrel, Gyan Prasad; Jalan, Aditya; Pradhan, Erena; Pokhrel, Bharatmani; Gharti, Binod Babu; Nepal, Umesh; Lamichhane, Nirmal (Nepalese Journal of Cancer, 2022)
Introduction: Renal cell carcinoma accounts for 3-5%of all oncological diagnoses. In this study, we aim to assess the clinicopathological profile of Renal cell carcinoma in a cancer hospital of Nepal. Method: This is a retrospective study conducted at BP Koirala Memorial Cancer hospital Nepal. All patients with localized and locally advanced RCC who underwent radical or partial nephrectomy at our hospital between Jan 2012 to Dec 2018 were included. Normally distributed continuous variables were expressed as median, mean ± standard deviation (SD). Categorical variables were expressed as frequencies and percentages of an appropriate denominator. Results: Among 94 patients with RCC, the median age was 55 years (53.56 ±12.83). Most of the patients were male (56.4%, n=53) and Hindu by religion (67.02%, n=63). Eighty-three percent (n=78) of patients were smokers, 58.5 % (n=55) were hypertensive and 40.4% (n= 38) had history of diabetes mellitus. The most common symptom was incidental renal mass (42.55%, n=40). Ninety-five percent (n=89) of the patients underwent radical nephrectomy and five percent (n=5) of the patients underwent partial nephrectomy. The median duration of postoperative hospital stay was 8 days. The most common histological finding was Clear cell type (86.17, n=81) followed by papillary cell type (10.63%, n= 10) followed by chromophobe type (2.12%, n=2), and duct of Bellini( 1.06%, n=1). Most of the patients had pathological T2 (41.48%, n=39) disease followed by T3 (26.59%, n=25) disease. Conclusion: Smoker males in the fifth to sixth decade of life are at risk for developing RCC. Radical Nephrectomy is the standard of care with Clear cell carcinoma as the most common histological subtype.